KEARIFAN LOKAL PETANI DAN KELESTARIAN GAMBUT (Studi Kasus: Desa Lukun Kecamatan Tebing Tinggi Timur Kabupaten Kepulauan Meranti Provinsi Riau) - Seger Sugiyanto; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Fires in 2015 and 2018 in the village of Lukun burned a total of about 310 hectares have serious consequences for nature and the local social environment. In addition to making some people lose their livelihoods, fires have also caused fauna migration and plant death. Furthermore, Peatland in Lukun Village has become critical and has even drought. By using the snowball technique, the author found 7 informants they are 3 sago farmers, 2 rubber farmers, 1 areca nut farmer, 1 vegetable farmer and banana. The type of research used was qualitative descriptive with 2 months of research duration. The findings of the study in terms of land preparation methods used are clear-cutting and cutting down the hallway. After a few days later, they start to burn the remaining wood or leaves. The Land cultivation and the seeds procurement are carried out with a system of